Efficiency of Growth Drivers An Analysis of Select Indian Industries - Chatterjee, Susmita (SpringerBriefs in Economics,, 2018)
This book covers three main areas, namely the pharmaceuticals industry, the telecommunications sector and the banking sector, with a focus on manufacturing and service. It includes a brief analysis of all three, particularly in the context of their evolution, current status, cost efficiency, and growth projections. The Indian pharmaceuticals market is the third-largest in the world in terms of volume and thirteenth-largest in terms of value; further, India is the world's largest provider of generic drugs. India is currently the second-largest telecommunications market and has the third-highest number of internet users in the world. At the same time, the deregulation of foreign direct investment (FDI) norms has made banking one of the fastest-growing sectors and a top-five employment opportunity generator in the country. Further, the efficiency and profitability of India's banking sector has assumed prime importance due to intense competition, customer demands and bank reforms. The book gauges the relative performance of the Indian banks based on certain key parameters. It then concisely presents the efficiency results, vividly portraying the industry's current status and serving as a ready reference that will be valuable to students, academics and industry experts alike. .